Demographic studies of Tribolium castaneum (Coleoptera: Tenebrionidae) on various barley cultivars. (December 2018) - Rahimi Namin, Foroogh; Naseri, Bahram; Nouri-Ganbalani, Gadir; Razmjou, Jabraeil
Abstract: Rust-red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), is one of the serious insect pests of cereal grains and other stored products throughout the world. In this research, demographic parameters of T. castaneum in response to feeding on ten barley cultivars (Behrokh, Bahman, Nosrat, Fajr 30, Makuyi, Sahra, Lout, Neek, Abidar and Sahand) were studied at 30 ± 1 °C, relative humidity of 75 ± 5% and darkness conditions. The longest larval period was on cultivars Makuyi and Fajr30, and the shortest period was on cultivar Lout. The fecundity, hatch rate, net reproductive rate, intrinsic rate of increase, and finite rate of increase was the lowest on cultivars Makuyi and Fajr30. Positive correlations were observed between the larval period, larval and pupal period, and doubling time with the grain hardness index. Moreover, there were negative correlations between the fecundity, hatch rate, R 0 and λ with the grain hardness index. The results showed that cultivars Makuyi and Fajr30 were unsuitable diets for feeding of T. castaneum, and could be suggested to be grown in areas with high potential for T. castaneum infestation. Graphical abstract: Highlights: Demographic parameters of T. castaneum were studied on ten barley cultivars. The lowest fecundity and hatch rate of T. castaneum were on cultivars Makuyi and Fajr30. The intrinsic rate of increase of T. castaneum was the lowest on cultivars Makuyi and Fajr30. Cultivars Makuyi and Fajr30 were unsuitable diets for feeding of T. castaneum .